1998
DOI: 10.1002/(sici)1097-0010(199810)78:2<149::aid-jsfa94>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Tillage and mulching effects on water use, root growth and yield of rainfed mustard and chickpea grown after lowland rice

Abstract: Crops grown under rainfed conditions are prone to water stress, owing to rapid loss of soil moisture and development of mechanical impedance to root growth. The stress can be alleviated by enlarging rooting volume in the soil and/or by regulating the supply of soil moisture. This study reports the effects of zero, minimum and conventional tillage with and without rice straw mulch on conservation of soil moisture, root growth and yield of chickpea and mustard grown under rainfed conditions for three years (1990… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 1 publication
7
41
2
1
Order By: Relevance
“…Soil beneath polyethylene mulch retained the greatest amount of water because soil temperatures were lower and polyethylene prevented water from evaporating quickly (Rathore et al, 1998;Mathews et al, 2002). In the case of the organic mulches, the values of the three parameters described above fall between those shown by polyethylene mulch and bare soil, because, although they absorbed energy and showed a greater SW than bare soil, they still lacked the ability of the polyethylene to reduce water loss.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Soil beneath polyethylene mulch retained the greatest amount of water because soil temperatures were lower and polyethylene prevented water from evaporating quickly (Rathore et al, 1998;Mathews et al, 2002). In the case of the organic mulches, the values of the three parameters described above fall between those shown by polyethylene mulch and bare soil, because, although they absorbed energy and showed a greater SW than bare soil, they still lacked the ability of the polyethylene to reduce water loss.…”
Section: Discussionsupporting
confidence: 90%
“…One of these is mulching, an agricultural technique which could favour the success of the planting, survival and growth of plants during reforestation, because it protects the soil structure from the impact of raindrops, reduces changes in temperature (Price et al, 1998), and the rate of evaporation decreases, while infiltration rate increases, losses due to erosion and water running off the surface are reduced (Rathore et al, 1998). However, in areas with water deficiencies, very little is known about the influence of mulches on the physical variables of the soil, as well as the changes in the microclimate and the plants survival (Tilander and Bonzi, 1997).…”
Section: María Guadalupe Barajas-guzmán and Víctor L Barradasmentioning
confidence: 99%
“…Similarly, lowest plant stand observed in treatment T 4 might be due to loss of soil moisture at the time of sowing and broadcasting of seeds. Rathore et al, (1998) also observed similar plant stand under zero tillage and minimum tillage. Significantly taller plant at all the crop growth stages were recorded with treatment T 2 as compared to rest of the treatments, however, it was found at par with treatment T 1 .…”
Section: Growth and Developmentmentioning
confidence: 99%
“…The even distribution of crop residues on the soil surface which blocks the direct evaporation from soil reduces the surface runoff. Besides, it acts as an insulator for solar radiation and do not permit direct contact with soil, which avoid continuity of capillaries for the evaporation loss of water through soil profile (Rathore et al, 1998). Higher soil moisture content under mulched plots than the no-mulched plots at all the soil depth was also reported by Pervaiz et al (2009).…”
Section: Variation In Soil Moisture Contentmentioning
confidence: 99%